pH-Responsive Liposomes of Dioleoyl Phosphatidylethanolamine and Cholesteryl Hemisuccinate for the Enhanced Anticancer Efficacy of Cisplatin - Hassan Shah; Asadullah Madni; Muhammad Muzamil Khan; Fiaz-; Nasrullah Jan; Safiullah Khan; Muhammad Abdur Rahim; Shahzeb Khan; Meser M. Ali; Mohsin Kazi (MDPI AG, 2022)
The current study aimed to develop pH-responsive cisplatin-loaded liposomes (CDDP@PLs) via the thin film hydration method. Formulations with varied ratios of dioleoyl phosphatidylethanolamine (DOPE) to cholesteryl hemisuccinate (CHEMS) were investigated to obtain the optimal particle size, zeta potential, entrapment efficiency, in vitro release profile, and stability. The particle size of the CDDP@PLs was in the range of 153.2 ± 3.08-206.4 ± 2.26 nm, zeta potential was −17.8 ± 1.26 to −24.6 ± 1.72, and PDI displayed an acceptable size distribution. Transmission electron microscopy revealed a spherical shape with ~200 nm size. Fourier transform infrared spectroscopic analysis showed the physicochemical stability of CDDP@PLs, and differential scanning calorimetry analysis showed the loss of the crystalline nature of cisplatin in liposomes. In vitro release study of CDDP@PLs at pH 7.4 depicted the lower release rate of cisplatin (less than 40%), and at a pH of 6.5, an almost 65% release rate was achieved compared to the release rate at pH 5.5 (more than 80%) showing the tumor-specific drug release. The cytotoxicity study showed the improved cytotoxicity of CDDP@PLs compared to cisplatin solution in MDA-MB-231 and SK-OV-3 cell lines, and fluorescence microscopy also showed enhanced cellular internalization. The acute toxicity study showed the safety and biocompatibility of the developed carrier system for the potential delivery of chemotherapeutic agents. These studies suggest that CDDP@PLs could be utilized as an efficient delivery system for the enhancement of therapeutic efficacy and to minimize the side effects of chemotherapy by releasing cisplatin at the tumor site.